STRATEGI PROMOSI MENINGKATKAN OCCUPANCY MELALUI MEDIA SOSIAL PASCA MASA PANDEMI COVID 19 RIEZ PALACE HOTEL TEGAL - Puput Dewi Anggraeni (Journal of Hospitality and Tourism, 2023)
The hospitality industry is a business that is most in demand by hoteliers in the world. This can be seen from the number of hotel businesses, including the hotel business in the Tegal City which is increasing because the occupancy rate or guest needs are getting higher. However, due to the pandemic, occupancy has dropped drastically. Therefore, it is necessary to carry out a promotional strategy through social media after the Covid 19 pandemic to increase occupancy at Riez Palace Hotel Tegal. This study aims to determine which social media promotion strategies are used by Riez Palace Hotel Tegal in promoting their hotels. This research was conducted at Riez Palace Hotel Tegal, and this research is a qualitative research. Data collection techniques used were observations, interviews, and documentation. The data obtained were analyzed using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The results showed that Riez Palace Hotel Tegal uses several social media as a strategy to promote the hotel so that occupancy can increase. Based on the results of the SWOT analysis, it is suggested that Riez Palace Hotel Tegal can implement the SO (StrengthsOpportunities) strategy.Keywords: occupancy; promotion strategy: social media